Pemberdayaan Kelompok Wanita Tani (KWT) di Kelurahan Kahuripan - Damay Rusli; Cicip Zemi Permadi; Dandan Haryono (Jurnal Indonesia Sosial Sains, 2022)
The empowerment of the Women Farmers Group has not been achieved properly as a result of the implementation of empowerment measures that have not been fully implemented by the Kahuripan Village Head and the Agricultural Extension Agency (BPP) of Kahuripan Village, Tawang District, Tasikmalaya City. The purpose of this study was to determine the empowerment of the Women Farmers Group (KWT) in Kahuripan Village, Tawang District, Tasikmalaya City. The method used in this study is a qualitative descriptive research method as a "Human Instrument" which functions to determine the focus of the research, select informants as data sources, collect data, select data quality, analyze data, interpret data and draw conclusions from the findings. from the information obtained. is in the field. From the results of the analysis, it can be concluded that the Empowerment of Women Farmers Groups has not been achieved properly because the empowerment measures have not been fully implemented, including: Opportunity Measures. So that the Empowerment of Women Farmers Groups in Kahuripan Village, Tawang District, Tasikmalaya City has not been achieved properly. From the explanation above, referring to the hierarchy of empowerment steps, community empowerment steps are very important to support the implementation of the Women Farmers Group in Kahuripan Village, Tawang District, Tasikmalaya City which has or has not been fully implemented optimally. , there needs to be improvements and improvements in the future in order to achieve organizational goals.